Dual band single layer microstrip antenna with circular polarization for WIMAX application - Noghabaei, Mohammad (IEEE, 2012)

(untitled)
A new configuration of a square patch Microstrip antenna for a single-feed to achieve a dual band frequency for WiMax application with circular polarization (CP) is proposed. A single layer is used for the antenna. Dual bandwidths and CP is achieved by designing asymmetrical slot and two different truncated corners. The radiation patterns demonstrate well cross polarization rejection and low back lobe radiations in directional orientation. The antenna has small size as well as good impedance matching bandwidth and is easy to fabricate. The compact microstrip antenna showed a good radiation characteristic with an impedance bandwidth of 4.6 % at the lower band (2.5 GHz) and 4.3 % at the upper band (5.7 GHz) and axial ratio of 2.1 % and 0.9% at the lower and upper band, respectively.